John the Water-Bearer (Ивань Водоносьць). Once Again on Dualism in the Bosnian Church - Minczew, Georgi (Studia Ceranea, 2020)
The article examines the debate as to the direct influence of Bulgarian and Byzantine Bogomilism upon the doctrine of the Bosnian Church. The author traces some scholarly views pro et contra the presence, in the Bosnian-Slavic sources, of traces of neo-Manichean views on the Church, the Patristic tradition, and the sacraments. In analyzing two marginal glosses in the so-called Srećković Gospel in the context of some anti-Bogomil Slavic and Byzantine texts, the article attempts to establish the importance of Bulgarian and Byzantine Bogomilism for the formation of certain dogmatic and ecclesiological views in the doctrine of the Bosnian Church: the negative attitude towards the orthodox Churches, especially the Roman Catholic Church; the rejection of the sacrament of baptism and of St. John the Baptist; the rejection of the sacrament of confession, and hence, of the Eucharist. These doctrinal particularities of the Bosnian Church warrant the assertion that its teachings and liturgical practice differed significantly from the dogmatics and practice of the orthodox Churches. Without being a copy of the Bogomil communities, the Bosnian Church was certainly heretical, and neo-Manichean influences from the Eastern Balkans were an integral element of the Bosnian Christians’ faith.